Viktimisasi Terselubung pada Model Perempuan dalam Industri Fesyen Ditinjau dengan Teori Corporate Victimization of Women - Eirene Teresha Hansherina; Yani Osmawati (Universitas Budi Luhur, 2023)
The fesyen industry is one of the industries that determines the standard of beauty and ideal bodyimage for society. In the modeling profession, the demand to have a thin body is one of the mainconditions for success. However, this demand often results in the implementation of fad diets whichare detrimental to the health and well-being of women. This phenomenon often occurs covertly andis not widely accepted by society. Therefore, a new approach is needed to understand and overcomethe victimization of women in the fesyen industry. The concept of Corporate Victimization of Womenprovides a framework for reviewing the phenomenon of victimization of women in this industry. Thisstudy aims to show how the demands of the fesyen industry to have a thin body affect the adoptionof fad diets and cause hidden victimization of female models.